2007
DOI: 10.1518/155534307x264898
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of an Intuitive Operational Planning Process

Abstract: Although formal planning procedures are key parts of military doctrine, they may not be well suited to highly dynamic, time-pressured environments. The authors describe an intuitive planning process developed as an alternative to the procedure used by the Canadian Forces (CF). The Intuitive Operational Planning Process (IOPP) treats planning as a highly iterative process of incremental refinement in which a single course of action is elaborated and continually evaluated for its suitability. To examine the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…TTXs also provide "soft benefits" to participants, primarily through collaborative discussions that provide opportunities to interact and share perspectives with people from different backgrounds [25], and contribute to a shared mental model among the participants who are often colleagues [30]. Similarly, Lombriser et al [31] noted that TTXs implicitly helped coordinate with stakeholders.…”
Section: Tabletop Exercises and Wargamesmentioning
confidence: 99%
“…TTXs also provide "soft benefits" to participants, primarily through collaborative discussions that provide opportunities to interact and share perspectives with people from different backgrounds [25], and contribute to a shared mental model among the participants who are often colleagues [30]. Similarly, Lombriser et al [31] noted that TTXs implicitly helped coordinate with stakeholders.…”
Section: Tabletop Exercises and Wargamesmentioning
confidence: 99%
“…These have been developed from military experience and are embodied in military doctrine (Shortland et al, 2019). Although different nations have some unique variations, the common major steps are: clarifying the mission; assessing the situation; developing several courses of action; comparing the courses of action; selecting a course of action; developing orders (Bryant, Martin, Bandali, Rehak, Vokac, & Lamoureux, 2007; Matthews, 2014). The process is thorough, detailed and the emphasis is on applying a rigorous process of logical deduction to complex and ill‐structured situations in order to develop a sound plan.…”
Section: Military Decision Makingmentioning
confidence: 99%
“…Other NDM models have been developed that are better able to explain other aspects of decision making, such as the factors that can derail decision making (Shortland, Alison, & Barrett‐Pink, 2018). New decision‐making procedures have been proposed that are more aligned with recognition‐primed decision making (Ross, Klein, Thunholm, Schmitt, & Baxter, 2004), better suited to decision making under time pressure (Thunholm, 2005), or capitalising on intuitive thought (Bryant et al, 2007). For example, these methods begin with identifying a course of action that is subsequently refined, based on the insight that experts generate a good course of action upon recognising the situation, rather than generating several courses of action for evaluation only after rigorous analysis.…”
Section: Military Decision Makingmentioning
confidence: 99%
“…In the case of the intuitive operational planning process (IOP), as compared with the existing Canadian operational planning process, IOP may foster greater collaboration and commander involvement in planning (Bryant et al, 2007). In fact, Thunholm (2006) employed the RPM as a basis for developing a formal planning model, the planning under time pressure (PUT) model, which is currently employed as a tactical-level planning model within the Swedish Armed Forces.…”
Section: Introductionmentioning
confidence: 99%
“…Formal empirical evaluations of the prescriptive value of intuitive planning models, such as the RPM relative to the MDMP, have shown that intuitive models permit an increase in planning tempo and lead to plans that are more bold and better adapted to situational demands (Blendell, Molloy, Catchpole, & Henderson, 2002;Pascual, Blendell, Molloy, Catchpole, & Henderson, 2001;Thunholm, 2005). In the case of the intuitive operational planning process (IOP), as compared with the existing Canadian operational planning process, IOP may foster greater collaboration and commander involvement in planning (Bryant et al, 2007). In fact, Thunholm (2006) employed the RPM as a basis for developing a formal planning model, the planning under time pressure (PUT) model, which is currently employed as a tactical-level planning model within the Swedish Armed Forces.…”
Section: Introductionmentioning
confidence: 99%